Characteristics of young adults with multiple episodes of diabetic ketoacidosis. Issue 7 (11th July 2019) - Gupta, Akhil; Taylor, Fiona; O'Sullivan, Terrianne; Simmons, David
Abstract: Transition from paediatric to adult diabetes care can be associated with a deterioration in metabolic control and hospitalisation. This was a retrospective review (2012–2016) of medical records of all patients attending a transition diabetes clinic in a teaching hospital with paediatric and adult diabetes on the same site. Among the 91/102 (89.2%) patients with type 1 diabetes, mean age at first visit was 19 ± 2 years, last body mass index was 25.2 ± 4.7 kg/m 2, diabetes duration was 11 ± 6 years and 22 (24%) used continuous subcutaneous insulin infusions. Loss to follow‐up was 15 (14.7%). Mental health issues were common (59%), as were prior pregnancies (23%) and diabetic ketoacidosis since diagnosis (39%). Those with diabetic ketoacidosis had a higher mean glycated haemoglobin (70 ± 19 vs 86 ± 25 mmol/mol or 8.6 ± 1.7 vs 10.0 ± 2.3%; P = 0.001), fewer clinic attendances (8 ± 5 vs 5 ± 4; P = 0.008) and fewer years in clinic (1.8 ± 1.7 vs 2.3 ± 1.4; P = 0.114). Our data suggest that investment in joint approaches with mental health services should be considered.